'In defence of the empire': Mauritius' government slaves in eighteenth-century Mauritius. (6th January 2022) - Teelock, Vijayalakshmi
Abstract: Mauritius' Government slaves form a unique body of slaves emerging out of its French colonial past. Slaves bought by the colonial administration formed part of the 'public works' department and built the infrastructure of the islans as well as manning forts, manufacturing gunpowder and even being recruited in the French naval squadrons going to fight the British in India.